PENANGANAN PERIOPERATIF PADA ASMA - Suhartono, Christina; Tambajong, Harold F; Lalenoh, Diana Ch. (Jurnal Biomedik : JBM, 2013)
Abstract: The management of a patient with asthma during surgery requires a special treatment based on thorough clinical and laboratory examinations to reduce complications during surgery and the post-operative state. Asthma is characterized by a difficulty in breathing due to spastic contractions of bronchiolar smooth muscles, which partially block the bronchioles’ airways. The evaluation of asthma patients before anesthesia and surgical procedures is essential to prevent or control the occurence of asthma attacks during intra-operation and post-operation. Patients with histories of chronic asthma or frequent exacerbations of asthma have to be treated to achieve an optimal condition or a condition in which asthma symptoms are minimal. Patients with frequent bronchospasms should be treated. The selection of drugs and anesthetic procedures should be considered meticulously to avoid a stimulation of  bronchospasm or an asthma attack. Keywords: asthma, perioperative management, patient.   Abstrak: Pengelolaan pasien dengan penyakit asma selama pembedahan membutuhkan penanganan khusus berdasarkan pemeriksaan klinis dan laboratorium yang saksama untuk mengurangi komplikasi selama dan pasca pembedahan. Asma adalah kesukaran bernapas yang ditandai dengan kontraksi spastik otot polos bronkiolus, yang menyumbat bronkiolus secara parsial. Evaluasi pasien asma sebelum tindakan anestesia dan pembedahan sangat penting untuk mencegah atau mengendalikan kejadian serangan asma, baik selama pembedahan maupun pasca pembedahan. Pasien dengan riwayat asma berulang atau kronis memerlukan pengobatan hingga tercapai kondisi yang optimal untuk dilakukan operasi atau kondisi dimana gejala-gejala asma sudah minimal. Pasien dengan  bronkospasme berulang harus diobati terlebih dahulu. Pemilihan obat-obatan dan tindakan anestesia perlu dipertimbangkan dengan cermat untuk menghindari terjadinya bronkospasme atau serangan asma. Kata kunci: asma, penanganan perioperatif, pasien.